An investigation of economic growth, youth unemployment and inflation in ASEAN countries - Yen Vun Fung; Janice L. H. Nga (Faculty of Business, Economics and Accountancy, 2021)
This study examines the relationship and interaction between youth unemployment (YU), inflation (INFLA), and economic growth (GDP)of ASEAN countries: Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam from 1996 to 2019. This study aims to examine the relationship between youth unemployment, inflation, and economic growth throughout the selected period. The method of Panel Granger Causality test, Panel Autoregressive Distributed Log (ADRL) approach, Panel unit root test, Panel co-integration test, Mean Group and Pooled Mean Group, and MANOVA test was applied in this study. This study found that in long run youth unemployment as a significant in negative impact where the increase in 1percent of youth unemployment, it will decrease 0.24 percent of economic growth. For inflation, the result stated that inflation also has positive significant impact in the long run which means that the increase 1percent in inflation, it also improves the economic growth with 0.31percent. As in ASEAN countries, the bidirectional relationship between youth unemployment, inflation and economic growth exist with causality running from youth unemployment and inflation to economic growth in individual. Lastly, youth unemployment and inflation have an interaction and is a significant effect on economic growth. Therefore, it is recommended that ASEAN countries take the specific policies that are effective and impact youth unemployment, inflation, and economic growth for the ASEAN countries. This research is expected to help enhance youth empowerment quality policies and improve the development of youth employment.